International tax planning in e-business - Tim, Artur (Funkcjonowanie e-biznesu. Zasoby, procesy, technologie, 2015)
International tax planning allows entrepreneurs to reduce income tax burden even to zero. Activities within the scope of the e-business have had an increasing importance over last years. Author proves that international tax law is not prepared for the challanges that digital economy poses for the Permanent Establisment concept. Such circumstances cause a risk (but also are a big hope) for entrepreneurs acting in the e-business structures – it is troublesome to recognise if website or server might be treated as the Permanent Establishement on the ground of double tax treaties. Author outlines the significance of international double taxation, OECD – and UN – Model Tax Convention, describes the essence of international tax planning and points out that there is a possibility to use the Permanent Establishment concept in the e-buisness in order to avoid taxes in a legal way.